1997
DOI: 10.1128/mcb.17.3.1201
|View full text |Cite
|
Sign up to set email alerts
|

Rho Family GTPases and Neuronal Growth Cone Remodelling: Relationship between Increased Complexity Induced by Cdc42Hs, Rac1, and Acetylcholine and Collapse Induced by RhoA and Lysophosphatidic Acid

Abstract: Rho family GTPases have been assigned important roles in the formation of actin-based morphologies in nonneuronal cells. Here we show that microinjection of Cdc42Hs and Rac1 promoted formation of filopodia and lamellipodia in N1E-115 neuroblastoma growth cones and along neurites. These actin-containing structures were also induced by injection of Clostridium botulinum C3 exoenzyme, which abolishes RhoA-mediated functions such as neurite retraction. The C3 response was inhibited by coinjection with the dominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
492
1
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 566 publications
(536 citation statements)
references
References 51 publications
39
492
1
1
Order By: Relevance
“…Several lines of evidence have suggested a functional antagonism between the Rac1/Cdc42 and RhoA-C subfamilies in controlling cytoskeletal structures (Kozma et al, 1997;Leeuwen et al, 1997;Moorman et al, 1999). As far as myogenesis is concerned, a similar balance between RhoG/Rac1/ Cdc42Hs and RhoA activities emerges in the light of the present study.…”
Section: Opposing Roles For Rhog/rac1/cdc42hs and Rhoa In Regulating supporting
confidence: 48%
“…Several lines of evidence have suggested a functional antagonism between the Rac1/Cdc42 and RhoA-C subfamilies in controlling cytoskeletal structures (Kozma et al, 1997;Leeuwen et al, 1997;Moorman et al, 1999). As far as myogenesis is concerned, a similar balance between RhoG/Rac1/ Cdc42Hs and RhoA activities emerges in the light of the present study.…”
Section: Opposing Roles For Rhog/rac1/cdc42hs and Rhoa In Regulating supporting
confidence: 48%
“…One could imagine a scenario in which weak inhibition of nucleotide exchange on endogenous Cdc42 by the N17 mutant might lead, through a feedback mechanism, to superstimulation of a GEF for the novel Rho-family GTPase. Others have noted a complex interplay in neuronal cells between the activation or inhibition of Cdc42 and Rac1 on the one hand and RhoA on the other, consistent with the idea that inhibition of one Rho-family GTPase can lead to the activation of other family members (Kozma et al, 1997).…”
Section: Discussionmentioning
confidence: 52%
“…LPA-induced actin polymerization results in process retraction and cell rounding in neuronal cells such as N1E-115, or stress fiber formation in fibroblast cells (Ridley and Hall, 1992;Jalink et al, 1993). These cellular responses are mediated by actomyosin interactions through activation of the Rho pathway, produc- ing contractile forces that induce cell shape changes (Jalink et al, 1994;Tigyi et al, 1996;Kozma et al, 1997;Hirose et al, 1998;Kranenburg et al, 1999;Fukushima et al, 2000;Weiner et al, 2001). Herein, we have also shown that Rho is activated by LPA in TR cells and LPA-induced process retraction is blocked by a ROCK inhibitor or CD, which indicates the possible involvement of Rho and actomyosin for process retraction in TR cells (Figure 10).…”
Section: Lpa Induces Both Actin Depolymerization and Polymerization Wmentioning
confidence: 63%